Accuracy of Mentzer index for predicting iron deficiency anemia in adults - Aslam, Farhan; Ilyas Dar, Savida; Azam Shah, Sara; Aqeel, Muhammad; Rehman, Abdur; Meraj, Lubna (International Journal of Pathology, 2024)
Background: It is of great clinical significance to differentiate between causes of microcytic, hypo chromatic anemias, iron deficiency anemia being one of them as it will improve with iron supplements. Complete blood picture is unable to differentiate. Iron studies and Hemoglobin electrophoresis are expensive tests. This necessitates the need of a cost-effective test and therefore we tried to determine the effectiveness of mentzer index in predicting iron deficiency anemia. Methods: It was an Observational, Cross-sectional study, conducted in Department of General Medicine, Federal government polyclinic hospital, Islamabad. Patients with microcytic hypochromic anemia, both from indoor and outdoor were included in study. Iron deficiency Anemia was diagnosed by iron studies (serum ferritin, Serum Iron, TIBC and transferrin saturation) and then mentzer index was calculated to check accuracy. Patient with normocytic or macrocytic anemia or other cell lines deficiency, patients with infectious diseases or inflammatory process were excluded from study. Results: A total of 155 patients were included in the study. Out of all the patients 145(93.5%) had mentzer index of > 13 while 10(6.5%) had mentzer index of <13. All of 150 patients (100%) had transferrin saturation lessthan 20 % indicating iron deficiency anemia against 93.5% picked up by Mentzer index. The receiver operator curves (ROC) showed that the MCV was the most important predictor of anemia while calculating mentzer index. The AUC value for MCV was 0.886(CI: 95%, 0.806-0.966, p value <0.000). MCV value between 52.6 to 63.5 fl predicted that the Mentzer index would be above 13, thus suggesting iron deficiency anemia with a sensitivity of more than 86%. Conclusion: Study findings support the use of Mentzer index, particularly MCV, as a valuable tool for predicting iron deficiency anemia.